APPLICATION OF GIS FOR ASSESSING PRAWN FARM DEVELOPMENT IN TULLY-CARDWELL, NORTH QUEENSLAND - Zainul Hidayah (Jurnal Kelautan, 2012)
In recent years, Geographical Information Systems (GIS) has been employed for various studies in aquaculture where geographical factors, natural resources and human activities are involved This study is intended to become a preliminary investigation for the development of prawn farm in Tully-Cardwell region of North Queensland. The aim of this research is to ident suitable sites for development of prawn farming using GIS multi-based criteria based on the basic requirements for prawn farming. Further analysis explains that 36,006.67 Ha of area which consists of 52 polygons are identiﬁed as suitable for the development of prawn farm in the region.Keywords: GIS, prawn farm, Queensland